Secure and Efficient Anonymous Authentication Scheme in Global Mobility Networks - Jun-Sub Kim; Jin Kwak (Journal of Applied Mathematics)
In 2012, Mun et al. pointed out that Wu et al.’s scheme failed to achieve user anonymity and perfect forward secrecy and disclosed the passwords of legitimate users. And they proposed a new enhancement for anonymous authentication scheme. However, their proposed scheme has vulnerabilities that are susceptible to replay attack and man-in-the-middle attack. It also incurs a high overhead in the database. In this paper, we examine the vulnerabilities in the existing schemes and the computational overhead incurred in the database. We then propose a secure and efficient anonymous authentication scheme for roaming service in global mobility network. Our proposed scheme is secure against various attacks, provides mutual authentication and session key establishment, and incurs less computational overhead in the database than Mun et al.'s scheme.